International Prices and Endogenous Quality * - Feenstra, Robert C.; Romalis, John (Quarterly Journal of Economics, 2014)
The unit values of internationally traded goods are heavily influenced by quality. We model this in an extended monopolistic competition framework where, in addition to choosing price, firms simultaneously choose quality subject to nonhomothetic demand. We estimate quality and quality-adjusted price indexes for 185 countries over 1984–2011. Our estimates are less sensitive to assumptions about the extensive margin of firms than are purely “demand-side” estimates. We find that quality-adjusted prices vary much less across countries than do unit values and, surprisingly, the quality-adjusted terms of trade are negatively related to countries’ level of income.